2009
DOI: 10.2169/internalmedicine.48.2382
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in a Patient Suffering from Cardiac Injury Due to Severe Hydrogen Sulfide Poisoning: A Long-term Examination of the Process of Recovery of Heart Failure by Performing Nuclear Medicine Study

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Obviously, all the benefical cardioprotective actions of H 2 S are due to low concentrations, because even recent clinical reports highlight that H 2 S poisoning causes cardiac injury due not only to local hypoxemia of the heart, but also to selective organ toxicity of the myocardium …”
Section: Major Regulatory Roles Of H2smentioning
confidence: 99%
“…Obviously, all the benefical cardioprotective actions of H 2 S are due to low concentrations, because even recent clinical reports highlight that H 2 S poisoning causes cardiac injury due not only to local hypoxemia of the heart, but also to selective organ toxicity of the myocardium …”
Section: Major Regulatory Roles Of H2smentioning
confidence: 99%
“…Dramatically, 1007 cases of suicide attempts with H 2 S were reported in 2008 in Japan, presumably due to the availability of information of this substance over the internet regarding a new home-made method of making the gas [4,12]. Mortality varies from 2 to 6% according to different series [13].…”
Section: Introductionmentioning
confidence: 99%
“…The ECG changes exhibited were likely contributed to by the hyperkaelamia, however the trend towards, and eventual normalisation, of serum potassium levels pre-and peri-cardiac arrest, suggests that other factors may have played a role. Previous studies have suggested that myocardial toxicity in H 2 S poisoning can be secondary to cellular hypoxia and also selective organ toxicity for the myocardium [9]. Due to the rise in serum troponin level and ST elevation exhibited on the ECG it is likely that our patient had a myocardial infarction and this may have ultimately been the cause of his death.…”
Section: Discussionmentioning
confidence: 84%